Low-Grade Ductal Carcinoma In Situ: Improving Interobserver Reproducibility on the Path to Surveillance Strategies. Issue 3 (26th November 2019) - Alghamdi, Sarah A; Krishnamurthy, Kritika; Garces Narvaez, Sofia A; Algashaamy, Khaled J; Aoun, Jessica; Reis, Isildinha M; Recine, Monica A; Jorda, Merce; Poppiti, Robert J; Gomez-Fernandez, Carmen R
Abstract: Objectives: We aimed to determine the interobserver reproducibility in diagnosing low-grade ductal carcinoma in situ (DCIS). We also aimed to compare the interobserver variability using a proposed two-tiered grading system as opposed to the current three-tiered system. Methods: Three expert breast pathologists and one junior pathologist identified low-grade DCIS from a set of 300 DCIS slides. Months later, participants were asked to grade the 300 cases using the standard three-tiered system. Results: Using the two-tiered system, interobserver agreement among breast pathologists was considered moderate (κ = 0.575). The agreement was similar (κ = 0.532) with the junior pathologist included. Using the three-tiered system, pathologists' agreement was poor (κ = 0.235). Conclusions: Pathologists' reproducibility on diagnosing low-grade DCIS showed moderate agreement. Experience does not seem to influence reproducibility. Our proposed two-tiered system of low vs nonlow grade, where the intermediate grade is grouped in the nonlow category has shown improved concordance.